Political competition and rural welfare: Evidence from Pakistan - Kosec, Katrina; Haider, Hamza; Spielman, David J.; Zaidi, Fatima (Oxford University Press, 2018)
Can stronger political competition improve rural livelihoods in developing countries? We explore this question in rural Pakistan, showing that greater political competition in a Provincial Assembly (PA) constituency predicts significantly better access to publicly-provided infrastructure and amenities, but no changes in other public goods including perceived access to justice and security. Nonetheless, overall welfare effects appear to be positive: higher political competition predicts higher expenditures per capita, especially among land-poor households. It also predicts higher land values, greater land wealth, and lower land wealth inequality. Further, political competition increases land rental, possibly indicating improved functionality of land markets. Sensitivity analyses suggest that our estimates are unlikely to be substantially affected by omitted variable bias, and they are further similar to instrumental variables estimates. The findings are also robust to use of alternate measures of political competition. Greater provision of both public and private goods appears to explain welfare improvements.